2008
DOI: 10.1016/j.limno.2007.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sampling microhabitats with low coverage within the STAR/AQEM macroinvertebrate sampling protocol on stream assessment

Abstract: In the STAR/AQEM protocol microhabitats covering less than 5% of the sampling area were neglected. Driven by an ongoing discussion on the importance of these underrepresented microhabitats we tested the influence of sampling them. We investigated 48 streams representing 14 different stream types from all over Germany. Macroinvertebrates of underrepresented microhabitats were sampled in addition to the STAR/AQEM protocol. To ensure the method remains feasible in routine monitoring programmes the total sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…There appear to be very few studies on the effect of under-represented lotic habitats and the influence of additional taxa in biological assessment. However, Haase et al (2009) also found that multimetric assessment results were affected by sampling 'additional' microhabitats with low coverage across 48 sampling sites in Germany using the STAR/AQEM sampling protocols. Interestingly, Bonada et al (2006) compared two different macroinvertebrate sampling methodologies in Mediterranean stream systems on two different continents and found that they produced very similar results, expressed via metrics.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…There appear to be very few studies on the effect of under-represented lotic habitats and the influence of additional taxa in biological assessment. However, Haase et al (2009) also found that multimetric assessment results were affected by sampling 'additional' microhabitats with low coverage across 48 sampling sites in Germany using the STAR/AQEM sampling protocols. Interestingly, Bonada et al (2006) compared two different macroinvertebrate sampling methodologies in Mediterranean stream systems on two different continents and found that they produced very similar results, expressed via metrics.…”
Section: Discussionmentioning
confidence: 97%
“…However, Haase et al . () also found that multimetric assessment results were affected by sampling ‘additional’ microhabitats with low coverage across 48 sampling sites in Germany using the STAR/AQEM sampling protocols. Interestingly, Bonada et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Natural variation has been demonstrated to reduce the sensitivity of macroinvertebrate indicators to change (Clarke et al, 2006;Blocksom & Flortmersch, 2008). Variability in relation to space, time and sampling methods have been stated as significant factors that result in difficulties in identifying significant change in macro-invertebrate monitoring (Brooks et al, 2002;Sporka et al, 2006;Haase et al, 2008). The results suggest that macroinvertebrate indicators maybe too insensitive to consistently identify early progress following river rehabilitation interventions.…”
Section: Methodological Limitationsmentioning
confidence: 99%